A framework for defining weights of decision makers in group decision-making, using consistency between different multicriteria weighting methods. Issue 2 (4th May 2023) - Blagojević, Boško; Nordström, Eva-Maria; Lindroos, Ola
ABSTRACT: Most forest operations are complex problems that require the weights of relevant criteria – representing trade-offs between various economic, ecological, and social aspects of the problem – to be defined. Usually this is done by using multicriteria weighting method(s) in a group (participatory) context in order to include different opinions and to minimize risk of poor individual judgments. Furthermore, in group decision-making, the weights of decision makers (DMs) must be defined. However, no consensus exists on the best way to determine related weights assigned to DMs. For that purpose, we propose the consistency-based group decision-making framework (CGDF), which uses the expertise of a DM to weight the responses of the DM when deriving an overall group decision. The novel part of CGDF is the inter-weights consistency method (ICM) for evaluating the expertise of a DM based on the consistency of the weights the DM assigns to different criteria using different multicriteria weighting methods. We demonstrate the utility of ICM and CGDF by applying them to a decision-making problem from Swedish forest operations – defining weights of criteria relevant for designing the machine-trail network for driving in the forest terrain.